2018
DOI: 10.1002/humu.23584
|View full text |Cite
|
Sign up to set email alerts
|

RareRELNvariants affect Reelin-DAB1 signal transduction in autism spectrum disorder

Abstract: The Reelin-DAB1 signaling pathway plays a crucial role in regulating neuronal migration and synapse function. Although many rare heterozygous variants in the Reelin gene (RELN) have been identified in patients with autism spectrum disorder (ASD), most variants are still of unknown clinical significance. Also, genetic data suggest that heterozygous variants in RELN alone appear to be insufficient to cause ASD. Here, we describe the identification and functional characterization of rare compound heterozygous mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 49 publications
2
35
0
4
Order By: Relevance
“…Our patient (F2688-1) presents no HALD4 features, and besides ASD features shows macrocrania and ADHD. Another study from our research group identified in this patient two inherited missense pathogenic variants in RELN, altering reelin secretion and signal transduction in neuronal cells from this patient [Sánchez-Sánchez et al, 2018]. These results suggest that despite CACNA1H is considered an ASD gene, the de novo LoF variant identified is not the only cause of ASD in our patient and may contribute to the phenotype in an oligogenic model.…”
Section: Discussionmentioning
confidence: 57%
“…Our patient (F2688-1) presents no HALD4 features, and besides ASD features shows macrocrania and ADHD. Another study from our research group identified in this patient two inherited missense pathogenic variants in RELN, altering reelin secretion and signal transduction in neuronal cells from this patient [Sánchez-Sánchez et al, 2018]. These results suggest that despite CACNA1H is considered an ASD gene, the de novo LoF variant identified is not the only cause of ASD in our patient and may contribute to the phenotype in an oligogenic model.…”
Section: Discussionmentioning
confidence: 57%
“…The variations in DAB1 function might contribute to make one genetically susceptible to autism, supporting the view that a defect in the Reelin signaling pathway might be a predisposing factor for ASD. 10,11 More recently, Sánchez-Sánchez et al, using iPSC-derived neural progenitor cells (NPCs) from one patient with nonsyndromic ASD, suggested an abnormal interplay between Reelin-DAB1 and mTORC1 signaling pathways and further support a multihit model of nonsyndromic ASD risk, in which a coincidental occurrence of disrupting variants in convergent molecular pathways may contribute to ASD. 10 To evaluate the inheritance of this CNV, biological parents were studied by quantitative polymerase chain reaction (qPCR) and the technique showed that the father is a carrier of the same microdeletion.…”
Section: Casementioning
confidence: 97%
“…10,11 More recently, Sánchez-Sánchez et al, using iPSC-derived neural progenitor cells (NPCs) from one patient with nonsyndromic ASD, suggested an abnormal interplay between Reelin-DAB1 and mTORC1 signaling pathways and further support a multihit model of nonsyndromic ASD risk, in which a coincidental occurrence of disrupting variants in convergent molecular pathways may contribute to ASD. 10 To evaluate the inheritance of this CNV, biological parents were studied by quantitative polymerase chain reaction (qPCR) and the technique showed that the father is a carrier of the same microdeletion. However, it is not clear if haploinsufficiency of DAB1 gene may have an isolated role in the pathophysiology of autism, making it difficult to advise parents on this matter.…”
Section: Casementioning
confidence: 97%
“…Deletion of one copy of these genes should result in a 1.5 to 2-fold Fig. 3 Examples of studies utilizing iPSC models to study nonsyndromic idiopathic ASD [18,34,[49][50][51][52][53][54][55][56]. Studies are ordered by year with the most recent at the top and include the total number of XX and XY patient iPSCs used in the bar chart reduction in gene expression.…”
Section: An Ideal Scenariomentioning
confidence: 99%